Side by side Italian & English grammar - Nanni-Tate, Paola; Farrell, C. Frederick 1934- (McGraw-Hill, 2013)
A guide to Italian grammar for beginning and intermediate students of the language, featuring side-by-side comparisons of English and Italian grammar topics, including parts of speech, nouns, pronouns, adjectives, adverbs, conjunctions, interjections, prepositions, and verbs, and including exercises and an answer key.